Analisis Ketidakseimbangan Beban Instalasi Listrik Di Fakultas Teknik Universitas Udayana - Damianus Tambi, Kosmas; Setiawan, I N.; Budiastra, I N. (Jurnal SPEKTRUM; Vol 4 No 1 (2017): Jurnal SPEKTRUM, 2017)
The imbalance load on the electrical installation systems always the case and the cause of these imbalances is a burden sharing between phases (r phase , s phase, and t phase ) that is not balanced. As a result of imbalance in the load current it flows in the neutral phase of n. The current flowing in the neutral, causing losses. This research was conducted by analyzing the power loss in the balanced and unbalanced state at night on the campus of a University of UdayanaFaculty of Engineering on Jalan P.B. Sudirman. Based on the results of the analysis on load imbalance between phases at MDP1 and MDP2 has caused the power loss. Large power loss load balanced on MDP1 was 0,042 kW, and the unbalanced load of 0.055 kW. While the loss of load balanced of mdp2 was 0.28 kW, and the unbalanced load ofMDP2 was 0,35 kW. So the greater the imbalance load on an electrical installation, the greater the neutral current, and losses due to neutral current to ground was also greater.